Development of PBL-based history e-module integrated with Uma Lengge to improve historical thinking - Rosdiana; Sumiyati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study was motivated by students' low historical thinking skills and the limited teaching materials that integrate historical material with the local cultural context of Uma Lengge. These conditions indicate the need to develop more contextual learning resources to support the history learning process. This study aims to develop a PBL-based History E-Module integrated with the local wisdom of Uma Lengge to improve students' historical thinking. The research model used is 4-D R&D, which includes the stages of definition, design, development, and dissemination. The research subjects were 60 tenth-grade students from Wawo 1 Public High School, selected through cluster random sampling, with class X-3 as the experimental group and class X-4 as the control group. Data were obtained through historical thinking ability tests and non-test techniques such as observation, interviews, expert validation, and practicality questionnaires. The instruments included validation sheets, questionnaires, and tests. Data analysis was conducted descriptively, qualitatively, and quantitatively using normality and homogeneity tests, paired-samples t-tests, and N-Gain calculations. The results showed that expert validation of the material and media indicated a highly valid category with an average score of 89.3%. The practicality test conducted by teachers was 90.2% in the highly practical category, while students gave an average rating of 3.29 in the very good category. The effectiveness test showed a significant increase in historical thinking skills, with an average post-test score of 82.17 in the experimental class, compared with 65.17 in the control class. N-gain analysis showed a moderate increase (0.40) in the experimental class and a low increase (0.10) in the control class. This e-module has been proven valid, practical, and effective. This study recommends expanding the use of similar e-modules, providing teachers with training, and developing other teaching materials based on local wisdom.